Workplace Deviance as a Possible "Maladaptive Coping" Behavior Displayed in Association with Workplace Stressors. Issue 7 (3rd July 2019) - Hendy, Helen M.; Can, S. Hakan; Black, Pamela
ABSTRACT: The Threat Appraisal and Coping Theory suggests that in response to environmental stressors, individuals sometimes display "maladaptive coping" behaviors that may vent frustration immediately but worsen later psychosocial well-being. For example, employees exposed to workplace stressors may vent their frustration with workplace deviance including intentional poor performance, abuse of organizational resources, disrespect, and disruption of co-workers, but such workplace deviance may worsen their later psychological well-being. The present study examined workplace deviance as a possible "maladaptive coping" behavior displayed by 293 university employees (74.7% female; 90.4% White; mean age = 45.8 years; 43 administrators, 127 staff, 84 faculty). When three workplace stressors (high demand, low control, low support) were compared for their association with workplace deviance, only low support was significant. Furthermore, workplace deviance was significantly associated with negative psychosocial outcomes [poor self-esteem, health concerns, anger, post-traumatic stress disorder (PTSD) symptoms, poor job satisfaction, work-home conflict]. Finally, bootstrapping mediational analysis revealed that workplace deviance was a significant mediator between low support and each of the negative psychosocial outcomes. Results support the idea that workplace deviance is an example of "maladaptive coping" behavior that, when displayed in response to perceptions of low support from supervisors and co-workers, is associated with worse psychosocial outcomes for employees who display it. Stress reduction programs could educate employees that displaying workplace deviance in response to workplace stressors may harm their psychosocial well-being. Such programs could also guide employees to more "adaptive coping" behaviors in response to workplace stressors (such as seeking social support, exercise, and yoga).